1984
DOI: 10.1080/00362178485380101
|View full text |Cite
|
Sign up to set email alerts
|

Trichophyton rubrumand the chemotaxis of polymorphonuclear leucocytes

Abstract: In experiments with a Boyden-type chamber, both the cell wall and a cytoplasmic extract of Trichophyton rubrum acted as chemotaxigens for polymorphonuclear neutrophils in the production of neutrophil chemotactic factor from plasma. Activation of complement by the cytoplasmic extract to produce neutrophil chemotactic factor is shown to be predominantly through the alternative pathway and the cytoplasmic extract mimics the activity of the complementary system.In the acute inflammatory response of the skin to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Furthermore, we observed migration of lymphocytes and PNL's between keratinocytes in stratum spinosum. A variety of mechanisms, such as complement activation by the alternative pathway and lowmolecular-weight chemotactic factor production, have been described to elucidate the mechanisms by which infl ammatory cells are attracted to the sites of cutaneous fungal infection (7,8,11,17,23,24). Our ultrastructural observation of migration of leucocytes is also consistent with the light microscopic fi ndings of epidermal lymphohistiocytic infi ltration frequently encountered in spongiotic dermatitis (8).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, we observed migration of lymphocytes and PNL's between keratinocytes in stratum spinosum. A variety of mechanisms, such as complement activation by the alternative pathway and lowmolecular-weight chemotactic factor production, have been described to elucidate the mechanisms by which infl ammatory cells are attracted to the sites of cutaneous fungal infection (7,8,11,17,23,24). Our ultrastructural observation of migration of leucocytes is also consistent with the light microscopic fi ndings of epidermal lymphohistiocytic infi ltration frequently encountered in spongiotic dermatitis (8).…”
Section: Discussionsupporting
confidence: 78%
“…Phagocytic cells may then attack organisms by using either oxidative or nonoxidative mechanisms, leading to their removal (454). Several organisms, including dermatophytes, Candida species, and propionibacteria, activate the alternative pathway of the complement cascade, causing the production of molecules with chemotactic activity for neutrophils (106,353,462). In this way, neutrophils may be recruited into the skin by the presence of microorganisms.…”
Section: Skin Immune Systemmentioning
confidence: 99%
“…In experiments with a Boyden-type chamber a cytoplasmic extract of Trichophyton rubrum (CETr) induced a plasma-dependent chemotaxis of polymorphonuclear leucocytes (PMNs) [8]. Although no chemotaxis occured in the absence of plasma, chemotaxis was induced with use of CETr and plasma in which the complement had been inactivated by heat and it was concluded that CETr mimics the activity of the complement system in the production of neutrophil chemotactic factor (NCF).…”
mentioning
confidence: 98%
“…The results are discussed in relation to reports on the importance of serine esterases in PMN chemotaxis. The failure of PMNs to migrate into keratinized tissue infected with T. rubrum is noted and it is suggested that the high enzymic activities necessary for the colonization of keratinized tissue effect a breakdown of NCF.In experiments with a Boyden-type chamber a cytoplasmic extract of Trichophyton rubrum (CETr) induced a plasma-dependent chemotaxis of polymorphonuclear leucocytes (PMNs) [8]. Although no chemotaxis occured in the absence of plasma, chemotaxis was induced with use of CETr and plasma in which the complement had been inactivated by heat and it was concluded that CETr mimics the activity of the complement system in the production of neutrophil chemotactic factor (NCF).…”
mentioning
confidence: 99%